Volatile metabolites, quality and sensory parameters of "Ferrovia" sweet cherry cold stored in air or packed in high CO2 modified atmospheres. (15th July 2019) - Cozzolino, R.; Martignetti, A.; Cefola, M.; Pace, B.; Capotorto, I.; De Giulio, B.; Montemurro, N.; Pellicano, M.P.
Highlights: VOCs profiles, quality and sensory parameters of cold packaged "Ferrovia" sweet cherry. Explore VOCs as potential biomarkers in different Modified Atmosphere treatments. Correlation between VOCs profiles and sensory attributes was achieved. Abstract: Volatile organic compounds, quality and sensory attributes of sweet cherry cv "Ferrovia", cold packaged in Air or in different modified atmospheres (Low-O2  = 1% O2 /0.03% CO2 ; High-CO2  = 16% O2 /20% CO2 ; Mix = 1% O2 /20% CO2 ), were monitored until 21 days of conservation. Results showed that sweet cherry cv "Ferrovia" is sensitive to CO2 accumulation (over 20%) in low oxygen (about 1%) modified atmosphere, as showed by the increase in respiration rate, biosynthesis of fermentative volatile metabolites, and sensory perception of off-odours. However, High-CO2 treatment seemed to preserve quality and sensory traits, presumably due to the high initial concentration of O2 (16%) that could limit the synthesis of ethyl esters and γ-butyrolactone, keeping the accumulation of off-flavours below their sensory perception threshold. Finally, PLSR analysis allowed to select 1-pentanol as putative marker of sensory alteration and hexanal and 2-hexenal as possible predictors of freshness for "Ferrovia" sweet cherries.